Analisis Kadar Bahan Organik Pada Tanah Ultisol di Perkebunan Kelapa Sawit Fase TBM (Tanaman Belum Menghasilkan) dan TM (Tanaman Menghasilkan) - Yosephine, Ingrid Ovie; Maisarah, Maisarah; Guntoro, Guntoro; Lubis, Abdul Rahman (JURNAL AGROPLASMA, 2025)
Ultisol soil is soil with soil acidity problems, little organic material and low macro nutrients, so it has a big impact on the productivity of oil palm plants. Organic matter is one of the limiting factors and plays a very important role in nutrient delivery and as a nutrient buffer. This research was carried out at PT. Langkat Nusantara Kepong Kebun Tanjung Beringin Langkat Regency in Division 2 Immature Crops (TBM) and Mature Crops ™. From December 2023 to February 5 2024. This research aims to be able to determine the soil organic matter content in the Immature Plants (TBM) and Mature Plants ™ phases in ultisol soil in the oil palm plantations of PT. Langkat Nusantara Kepong Kebun Tanjung Beringin. This research used quantitative descriptive methods and a completely randomized design. Research Results: The organic C content of Tanjung Beringin gardens is relatively low. The C-organic content in the TBM area has a significant difference compared to the TM area. The N content of Tanjung Beringin garden soil is classified as very low and there is no significant difference between the TBM and TM areas. Keywords: ultisol soil, organic matter, palm oil, TBM, TM